Plant Therapeutics - Cheng, Juei-Tang; Liu, I-Min; Shen, Szu-Chuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue provides recent advances in the use of plants for therapeutic purposes. This Special Issue collected the plants, including leaf, fruit, and others. This Special Issue's targets were crude plant extract and active principle purified from the plant. This Special Issue prompted researchers to provide each plant discovery. We are pleased to include in this Special Issue the screened Mexican plants and the halophytic plants growing in central Saudi Arabia, and so on. As a result, we have sparked scientists' interest in studying the plant for therapeutic purposes. This field necessitates network pharmacology analysis and machine-aided learning. Many disorders resistant to modern medication are looking for active principles isolated from the plants all over the world.